Safety of Plasma Infusions in Parkinson's Disease. Issue 11 (7th July 2020) - Parker, Jordan E.; Martinez, Amaris; Deutsch, Gayle K.; Prabhakar, Varsha; Lising, Melanie; Kapphahn, Kristopher I.; Anidi, Chioma M.; Neuville, Raumin; Coburn, Maria; Shah, Neil; Bronte‐Stewart, Helen M.
Abstract: Background: Young plasma infusions have emerged as a potential treatment for neurodegenerative disease, and convalescent plasma therapy has been used safely in the management of viral pandemics. However, the effect of plasma therapy in Parkinson's disease (PD) is unknown. Objectives: The objective of this study was to determine the safety, tolerability, and feasibility of plasma infusions in people with PD. Methods: A total of 15 people with clinically established PD, at least 1 cognitive complaint, and on stable therapy received 1 unit of young fresh frozen plasma twice a week for 4 weeks. Assessments and adverse effects were performed/reported on and off therapy at baseline, immediately after, and 4 weeks after the infusions ended. Adverse effects were also assessed during infusions. The primary outcomes were safety, tolerability, and feasibility. Exploratory outcomes included Unified Parkinson's Disease Rating Scale Part III off medication, neuropsychological battery, Parkinson's Disease Questionnaire‐39, inflammatory markers (tumor necrosis factor‐α, interleukin‐6), uric acid, and quantitative kinematics. Results: Adherence rate was 100% with no serious adverse effects. There was evidence of improvement in phonemic fluency ( P = 0.002) and in the Parkinson's Disease Questionnaire‐39 stigma subscore ( P = 0.013) that were maintained at the delayed evaluation. Elevated baseline tumor necrosis factor‐α levels decreased 4 weeks after the infusions ended. Conclusions: Young fresh frozen plasma was safe, feasible, and well tolerated in people with PD, without serious adverse effects and with preliminary evidence for improvements in phonemic fluency and stigma. The results of this study warrant further therapeutic investigations in PD and provide safety and feasibility data for plasma therapy in people with PD who may be at higher risk for severe complications of COVID‐19. © 2020 The Authors. Movement Disorders published by Wiley Periodicals LLC on behalf of International Parkinson and Movement Disorder Society.